2014
DOI: 10.1021/es503163w
|View full text |Cite
|
Sign up to set email alerts
|

Light-Independent Reactive Oxygen Species (ROS) Formation through Electron Transfer from Carboxylated Single-Walled Carbon Nanotubes in Water

Abstract: Promising developments in application of carbon nanotubes (CNTs) have raised concern regarding potential biological and environmental effects upon their inevitable release to the environment. Although some CNTs have been reported to generate reactive oxygen species (ROS) under light, limited information exists on ROS generation by these materials in the dark. In this study, generation of ROS was examined, initiated by electron transfer from biological electron donors through carboxylated single-walled carbon n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 36 publications
(72 reference statements)
2
40
0
Order By: Relevance
“…It is well known that the presenceπ bonds in nanocarbons can promote electron-transfer reactions (which is also evident in our electrochemistry results described in Fig. 4) in biomolecules and can generate ROS by acting as redox mediators 37 . The DCF fluorescence intensity showed only slight changes in ROS levels for graphene and its associated amino acid complexes.…”
Section: Results and Discussion: As Shown Insupporting
confidence: 72%
“…It is well known that the presenceπ bonds in nanocarbons can promote electron-transfer reactions (which is also evident in our electrochemistry results described in Fig. 4) in biomolecules and can generate ROS by acting as redox mediators 37 . The DCF fluorescence intensity showed only slight changes in ROS levels for graphene and its associated amino acid complexes.…”
Section: Results and Discussion: As Shown Insupporting
confidence: 72%
“…This result gave us an implication that H 2 O 2 should not be the final reductive product and can be reduced further in the following reaction. Indeed, it had been reported that rGO can promote the decomposition of H 2 O 2 in the dark [20]. As mentioned above, OH was also found to take part in the oxidative coupling reaction of MOP.…”
Section: Role Of Domentioning
confidence: 81%
“…Firstly, the carbon atoms in carbon materials are either sp 2 or sp 3 hybridized, while the sp 2 hybridized carbon atoms are able to participate in electro-transfer reactions. The singlewalled carbon nanotube is known to act as redox mediator in some biological systems which uses the large array of conjugated C¼C bonds to shuttle electrons from biological electron donors to electron acceptors [20,21]. Secondly, since nearly all carbon surfaces are prone to reactions with O 2 and H 2 O, oxygencontaining groups are present on a vast majority of carbon materials [5].…”
Section: Mechanism Involved In the Degradation Of Rhb At The Graphitementioning
confidence: 99%
“…Specifically, in the presence of O 2 this process is dominated by the anode-catalyzed O 2 -oxidation mechanism in which the O 2 performs as the oxidant and the unsaturated functional groups in graphite play a catalyzing role. Such a catalytic reaction is analogue to that happens on the carbon nanotubes, in which the O 2 is firstly absorbed on the carbon nanotubes and then added across the C¼C bond to form transition species with reaction characteristics resemble to that of the peroxyl radical [21,25]. Since the RhB is partially degraded rather than totally mineralized, the anode-catalyzed O 2 -oxidation mechanism presents lower oxidation power than the OH oxidation mechanism.…”
Section: Mechanism Involved In the Degradation Of Rhb At The Graphitementioning
confidence: 99%